2013
DOI: 10.1159/000350791
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of the Immunodominant Regions of Shrimp Tropomyosin Pan b 1 by Human IgE-Binding and IgE Receptor Crosslinking Studies

Abstract: Background: Epitope mapping of an allergen is generally done by IgE-binding assays with short synthetic peptides, but this provides little information about which domains are responsible for IgE receptor crosslinking on effector cells. Our aim was to map the immunodominant regions of shrimp tropomyosin by both IgE-binding and IgE-receptor crosslinking studies. Methods: Five overlapping fragments covering Pandalus borealis tropomyosin were cloned, expressed in Escherichia coli and characterized by circular dich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…For the small fraction that do form dimers based upon SDS-PAGE analysis, it is intriguing to note that the coiled-coil orientation of two identical epitopes in any pair of dimers renders their distance very close (<2 nm). Our preparations showed reduced allergenicity by comparison to an earlier study (51), presumably due to differences in design, affinity purification and/or concentration steps that will be critical to carry forward for potential clinical development.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…For the small fraction that do form dimers based upon SDS-PAGE analysis, it is intriguing to note that the coiled-coil orientation of two identical epitopes in any pair of dimers renders their distance very close (<2 nm). Our preparations showed reduced allergenicity by comparison to an earlier study (51), presumably due to differences in design, affinity purification and/or concentration steps that will be critical to carry forward for potential clinical development.…”
Section: Discussionmentioning
confidence: 55%
“…While pepsin-cleaved fragments of natural Pen a 1 are potent initiators of degranulation, it has been reported that short, recombinant Pen a 1-derived polypeptides encompassing a single predominant IgE binding epitope have diminished capacity (51). As shown in Figure 5A, we designed and expressed five sequential Pen a 1-recombinant polypeptides (FR1 1–79 , FR2 68–127 , FR3 121–181 , FR4 172–236 , FR5 224–284 ), each 60–79 amino acids in length.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proliferative responses of splenocytes from mice immunized with either rAed a 10.01 or rAed a 10.02 to different concentrations of all recombinant tropomyosins were assessed ( Figure 5A,B). rAed a 10.01-immunized mice showed stronger proliferative responses to Nevertheless, the T cell-activating regions Aed a 10.01 [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] , Aed a 10.01 111-130 , Aed a 10.01 [161][162][163][164][165][166][167][168][169][170][171][172][173][174][175][176][177][178][179][180] and Aed a 10.01 221-270 corresponded to T cell-activating regions in shrimp tropomyosin previously identified in humans. 19 Furthermore, these regions are highly conserved within the amino acid sequences of all tropomyosins and show 55%-100% of sequence identity (70%-100% of similarity)…”
Section: Murine T Cells Specific For a Aegypti Tropomyosins Cross-mentioning
confidence: 99%
“…Purified natural and recombinant Pan b 1 at 0.5 μg/ml (15 μ M ) activated basophils to a similar degree as 1 μg/ml of shrimp extract [58]. BAT with molecular allergen Ara h 2 is good at identifying true peanut-allergic Mediterranean patients and distinguishing them from peach-allergic patients [59].…”
Section: Progress In the Diagnosis And Monitoring Of Allergy By Basopmentioning
confidence: 99%